The functional vascular anatomy of the swine for research. (April 2022) - Edwards, Joseph; Abdou, Hossam; Patel, Neerav; Madurska, Marta J; Poe, Kelly; Bonin, Janet E; Richmond, Michael J; Rasmussen, Todd E; Morrison, Jonathan J
Objectives: Swine ( Sus Scrofa ) are utilized broadly in research settings, given similarities to human vessel size and function; however, there are some important differences for clinicians to understand in order to interpret and perform translational research. This review article uses angiograms acquired in the course of a translational research program to present a description of the functional anatomy of the swine. Methods: Digital subtraction angiography and computed tomography angiography were obtained throughout the course of multiple studies utilizing power injection with iodinated contrast. Subtracted two-dimensional images and three-dimensional multiplanar reformations were utilized post image acquisition to create maximal intensity projections and three-dimensional renderings of using open-source software (OsiriX). These imaging data are presented along with vessel measurements for reference. Results: An atlas highlighting swine vascular anatomy, with an emphasis on inter-species differences that may influence how studies are conducted and interpreted, was compiled. Conclusions: Swine are utilized in broad-reaching fields for preclinical research. While many similarities between human and swine vasculature exist, there are important differences to consider when conducting and interpreting research. This review article highlights these differences and presents accompanying images to inform clinicians gaining experience in swine research.